Heredity as a factor in the formation of recurrent depression - N. Maruta; S. Kolyadko; T. Panko; O. Semikina (European Psychiatry, 2022)
Introduction At the current stage of psychiatry development, special attention is paid to studying the influence of hereditary factors on the occurrence of recurrent depression (RD). The study can be informative in predicting the risk of the RD occurrence RD. Therefore, studies related to this problem are designed to identify the specificity “familial” forms of RD.